Intramuscular Hemangioma: A Rare Cause of Omalgia - Pedro M. Guedes; Nuno A. Saldanha; Pedro M. Matos; Francisco S. Carvalho; Graça Veiga; Pedro Norton (Revista Brasileira de Ortopedia, 2023)
Abstract Intramuscular hemangiomas (IHs) are benign soft-tissue tumors that represent less than 1% of all hemangiomas. This clinical entity is rarely considered as a differential diagnosis in cases of musculoskeletal pain. A healthy 38-year-old woman presented to our office with complaint of left omalgia, with 8 months of evolution, limiting her daily activities. She reported the appearance of tumefaction in the previous 4 months. She was medicated with analgesic and antiinflammatory drugs with no clinical improvement. The objective examination showed limitation of left shoulder abduction (0–90°). The patient underwent a magnetic resonance imaging (MRI), in which a well-circumscribed nodular formation was detected in the deltoid muscle. Then, she underwent a biopsy, which confirmed the diagnosis of hemangioma. The patient was referred for sclerotherapy. Intramuscular hemangiomas are usually observed in young patients. The gold-standard examination for diagnosis is MRI, which often forestalls the need for a biopsy. In many cases, IHs are asymptomatic and tend to involute over time. Despite the low frequency of this clinical entity, it is important to place it as a diagnostic hypothesis in cases of chronic pain of the limbs in young patients with poor therapeutic response to antiinflammatory drugs and analgesia.